Dentists' perspectives on caries-related treatment decisions (2020)
Objective: To assess the impact of patient risk status on Colombian dentists’ caries related treatment decisions for early to intermediate caries lesions (ICDAS code 2 to 4). Methods: A web-based questionnaire assessed dentists’ views on the management of early/intermediate lesions. The questionnaire included questions on demographic characteristics, five clinical scenarios with randomised levels of caries risk, and two questions on different clinical and radiographic sets of images with different thresholds of caries. Results: Questionnaires were completed by 439 dentists. For the two scenarios describing occlusal lesions ICDAS code 2, dentists chose to provide a preventive option in 63% and 60% of the cases. For the approximal lesion ICDAS code 2, 81% of the dentists chose to restore. The main findings of the binary logistic regression analysis for the clinical scenarios suggest that for the ICDAS code 2 occlusal lesions, the odds of a high caries risk patient having restorations is higher than for a low caries risk patient. For the questions describing different clinical thresholds of caries, most dentists would restore at ICDAS code 2 (55%) and for the question showing different radiographic thresholds images, 65% of dentists would intervene operatively at the inner half of enamel. No significant differences with respect to risk were found for these questions with the logistic regression. Conclusion: The results of this study indicate that Colombian dentists have not yet fully adopted non-invasive treatment for early caries lesions. Key words: caries detection, clinical decision-making, treatment thresholds, caries management, Colombia, general dental practitioners